Malaysia-Qatar relationship: perspective from Malaysia: an emerging middle power - Hossain, Ishtiaq; Shukri, Syaza Farhana Mohamad (2018)
This paper purports to provide a perspective from Malaysia on the country’s relationship with Qatar. It is held in this paper that Malaysia is an emerging middle power, and therefore, Malaysia’s relationship with Qatar is better analysed within the context of foreign policy behaviour of an emerging middle power. The concept of an emerging power would be defined. But before doing it, we will provide justification for this study. Then an attempt is made to discuss the foreign policy behaviour of Malaysia as an emerging middle power. It is undeniable that the current topsy-turvy international system is influencing the conduct of international relations of all states. Malaysia is no exception. So, this paper provides an analysis of the major factors that are affecting the contemporary international system. Malaysia’s domestic political order went through changes as a result of Malaysia’s General Elections (GE-14) held in May,2018. This paper would identify those changes, and explain their impact on foreign policy of Malaysia, in particular, this paper looks at those factors that are likely to impact on Malaysia’s relations with Qatar. Next, the paper discusses the state of Malaysia-Qatar trade and economic ties. This is followed by a general discussion on steps to be taken to further improve the trade and economic ties between the two counties.